Changes in the impact of US macroeconomic news on financial markets the example of the Warsaw Stock Exchange - Henryk Gurgul; Jessica Hastenteufel; Tomasz Wójtowicz (Statistics in Transition New Series, 2021)
Due to the high importance of the American economy, in the past, announcements of US macroeconomic data were shown to have a significant impact on financial markets in general, and on European stock markets in particular. However, as this effect may vary in time, this paper examines the changes in the impact of US macroeconomic news on the WIG20, the main index of the Warsaw Stock Exchange. Based on intraday data from 2004-2019 we study the changes in significance and in the strength of the reaction of WIG20 to announcements of unexpected values of 13 indicators describing the American economy. On the basis of the event study analysis, we describe the reaction of the WIG20 index in the first few minutes after these kinds of announcements.
Keywords: 519; event study; macroeconomic announcements; intraday data; Warsaw Stock Exchange